2006
DOI: 10.1128/aac.00149-06
|View full text |Cite
|
Sign up to set email alerts
|

Replicon Typing of Plasmids Carrying CTX-M or CMY β-Lactamases Circulating among Salmonella and Escherichia coli Isolates

Abstract: Replicon typing of plasmids carrying bla CTX-M or bla CMY ␤-lactamase genes indicates a predominance of I1 and A/C replicons among bla CMY -carrying plasmids and five different plasmid scaffolds associated with the different types of bla CTX-M genes (I1, FII, HI2, K, and N). These results demonstrate the association of certain ␤-lactamase genes with specific plasmid backbones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
130
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 15 publications
15
130
2
Order By: Relevance
“…Association of the bla CTX-M-15 gene with IncFII replicons has been described in studies conducted in Canada, France, Spain, and the United Kingdom (5,7,8,17,19). Although we observed intercontinental dissemination of 3 major IncFII plasmid scaffolds (A, B, and C) carrying bla CTX-M-15 , similarity >70% among all variants studied and presence of genes also found in pC15-1a, a CTX-M-15 plasmid (GenBank accession no.…”
Section: Discussionmentioning
confidence: 65%
“…Association of the bla CTX-M-15 gene with IncFII replicons has been described in studies conducted in Canada, France, Spain, and the United Kingdom (5,7,8,17,19). Although we observed intercontinental dissemination of 3 major IncFII plasmid scaffolds (A, B, and C) carrying bla CTX-M-15 , similarity >70% among all variants studied and presence of genes also found in pC15-1a, a CTX-M-15 plasmid (GenBank accession no.…”
Section: Discussionmentioning
confidence: 65%
“…CTX-M-15 is a class A ESBL encoded by the bla CTX-M-15 gene, which has been identified in plasmids of varying size (85-200 kb) and structure, and often belonging to the FII incompatibility (Inc) group [4]. OXA-48 is an Ambler class D carbapenemase that confers resistance to penicillins and reduced susceptibility to carbapenems but does not significantly hydrolyse broad-spectrum cephalosporins [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, plasmids harboring aphA1, aadA1, tetA, and sul1 were IncP type. Previous reports indicated that IncI1 plasmids harboring bla CTX-M-14 were detected in Salmonella enterica serovar Enteritidis (S. Enteritidis) [7] and E. coli bacteria [15]. It's worth noting that several studies describing the occurrence of CTX-M-14 ESBL in S. Enteritidis isolated from human patients in Spain [17], Hong Kong [10] and Japan [9] have been reported since 2003.…”
mentioning
confidence: 99%